An ecological study of Rotifera of the Southern Shatt Al-Arab River, Basrah, Iraq - Mohammed F. Abbas (المجلة العراقية للاستزراع المائي, 2022)
At three stations of the Shatt Al-Arab River, the ecology of Rotifera was studied: the first Al-Ashar second Abul Khasib and the third Al-Fao. Seasonal horizontal hauls were taken by a plankton net of a mesh-size of 53-µm during 2013. Density of Rotifera fluctuated between 0-113.3 ind./L registered at all station. Eighteen taxa belonging to nine genera of Rotifera were encountered. Water temperature values ranged between 15 and 27.5 degrees Celsius, salinity values were registered 1.8-40 g/L, pH values ranged between 6.2 and 8.7, and the dissolved oxygen values ranged between 5.1 and 9.9 mg/L.  TDS values fluctuated between 1467 and 33590 mg/L, while the turbidity values ranged between 7.1 and 180.6 FTU. Data were statistically analyzed using SPSS and CANOCO software.